Cranial Base Measurements in Skeletal Malocclusion among Orthodontic Patients - Pant, Bashu Dev; Rajbhandari, Anjana; Pradhan, Resina; Bajracharya, Manju; Maharjan, Surendra (Journal of Nepal Health Research Council, 2024)
Background: Facial growth and development is necessary for proper orthodontic diagnosis and treatment planning. Growth of cranial base is linked to the overall growth of facial bones, especially the maxilla and mandible. Any change in the amount and direction of growth of the cranial base can have direct or indirect effects on the developing maxilla and mandible. Thus the aim of this study was to determine the linear and angular cranial base measurements in different skeletal malocclusion in Nepalese population.Methods: Pretreatment lateral cephalograms of 225 patients aged between 17-30 years were collected. Linear measurements Sella-Nasion (S-N), Sella-Articulare (S-Ar), Articulare-Gonion (Ar-Go), Gonion-Gnathion (Go-Gn) and angular measurements Saddle angle (N-S-Ar), Articular angle (S-Ar-Go) and Gonial angle (Ar-Go-Gn) were measured.Results: In angular measurements statistically significant differences were found in the saddle and gonial angles between class I, II, and III skeletal pattern. In linear measurements, anterior and posterior cranial base lengths were not significantly different among groups however, ramal height and mandibular body length were significantly different among groups with a P value < 0.05.Conclusions: Skeletal class III has a larger gonial angle, ramal height and mandibular length. Males have larger linear measurements and females have larger angular measurements. Keywords: Cephalogram; Cranial base; Skeletal malocclusion